INTEGRASI TEKNOLOGI MULTIMEDIA DALAM PEMBELAJARAN KOMUNIKASI DAN PENYIARAN ISLAM UNTUK MENINGKATKAN KOMPETENSI DAKWAH DIGITAL MAHASISWA - Ely Suwaibatul Aslamiyah (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2025)
Advances in telecommunication and multimedia technologies have transformed approaches to Islamic da'wah and education. Islamic higher education institutions must equip students with digital communication skills suited to the 5G era. This study examines the use of multimedia technology in Islamic Communication and Broadcasting (KPI) learning and its impact on digital da'wah competence. Using a mixed-methods sequential explanatory design, quantitative data were collected from 120 KPI students in East Java, and qualitative data from interviews with 10 lecturers. Results show that interactive multimedia significantly enhances students’ creativity, technical skills, and digital literacy. The study underscores the need for a KPI curriculum oriented toward digital content creation.